Facile Fabrication of Alginate–BiBDC Composite Beads for Efficient Removal of Methylene Blue from Aqueous Solutions - Nguyen Duy Thanh; Nguyen Truong Thi; Van Cuong Nguyen; Hoang Ai Le Pham (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2026)
Alginate–BiBDC composite beads were produced using Ca²⁺-mediated ionic crosslinking and assessed for methylene blue (MB) adsorption. FT-IR, XRD, SEM, BET, and TGA validated the effective incorporation of BiBDC and the creation of a porous hybrid network. Among the composites, ALG@BiBDC-2 exhibited the most advantageous textural characteristics (14.16 m².g⁻¹ surface area, 0.0324 cm³.g⁻¹ pore volume, 16.27 nm pore size), attaining 85.33% methylene blue removal within 60 min. Adsorption was significantly influenced by pH, dose, concentration, and temperature. At a pHPZC of 6.76, electrostatic attraction predominates in the uptake of MB. The adsorption process followed a pseudo-second-order model and a Langmuir isotherm, indicating chemisorption-driven monolayer adsorption. Thermodynamic analysis validated spontaneous and exothermic characteristics. The beads maintained over 60% effectiveness after four cycles, indicating moderate stability and significant promise for treating dye-contaminated wastewater. Copyright © 2026 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).